Does Plasma Inhibit the Activity of KCl Cotransport in Red Cells From LK Sheep? - Lu, David C.-Y.; Hannemann, Anke; Gibson, John S. (Frontiers in Physiology, 2022)
Red cells from LK sheep represent an important paradigm for control of KCl cotransport activity, as well as being important to sheep erythroid function. A previous report (Godart et al., 1997) suggested that autologous plasma markedly inhibits red cell KCC activity and identified the presence of the bicarbonate / CO2 buffer system as the probable cause. Findings were restricted, however, to red cells from patients with sickle cell disease (SCD) swollen anisotonically and carried out at a very high O2 tension (c.700 mmHg). It was therefore important to investigate the generality of the effect described and whether it was also relevant to the two main stimuli for KCC activity encountered most often by circulating red cells in vivo - low pH in active muscle beds during exercise and high urea concentrations in the renal medulla during antidiuresis. Results confirm that inhibition was significant in response to anisotonic swelling with KCC activity in MOPS-buffered saline (MBS) vs bicarbonate-buffered saline (BBS) and in MBS vs plasma both reduced (by about 25 and 50 %, respectively). By contrast, however, inhibition was absent at low pH and in high concentrations of urea. These findings suggest therefore that red cell KCC activity represents an important membrane permeability in vivo in red cells suspended in plasma. They are relevant, in particular, to sheep red cells, and may also be important by extension to those of other species and to the abnormal red cells found in human patients with SCD.